2016
DOI: 10.1089/end.2015.0864
|View full text |Cite
|
Sign up to set email alerts
|

An Ex Vivo Phantom Validation Study of an MRI-Transrectal Ultrasound Fusion Device for Targeted Prostate Biopsy

Abstract: MRI-TRUS fusion allows for accurate sampling of MRI-identified lesions with an OE of 2.33 mm. Lesions with a diameter of 3 mm or more can be accurately targeted. These results should be considered the lower limit of in vivo accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Seifabadi et al evaluated the prostate biopsy needle placement accuracy of an MRI-guided robot and found overall system error in phantoms to be 2.5 mm [ 25 ]. Wegelin et al assessed the ex vivo accuracy of an MRI-TRUS fusion guidance device and found the mean overall error in the transverse plane to be 2.33 mm [ 26 ]. In a different study of a 3D ultrasound-guided transrectal biopsy system, the mean needle-segment-to-target distance was 3.6 ± 4.0 mm and mean needle-to-target distance was 3.2 ± 2.4 mm [ 27 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Seifabadi et al evaluated the prostate biopsy needle placement accuracy of an MRI-guided robot and found overall system error in phantoms to be 2.5 mm [ 25 ]. Wegelin et al assessed the ex vivo accuracy of an MRI-TRUS fusion guidance device and found the mean overall error in the transverse plane to be 2.33 mm [ 26 ]. In a different study of a 3D ultrasound-guided transrectal biopsy system, the mean needle-segment-to-target distance was 3.6 ± 4.0 mm and mean needle-to-target distance was 3.2 ± 2.4 mm [ 27 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Несмотря на преимущества, МРТ имеет ограничения в применении в клинической практике. Например, при небольших опухолях, которые трудно визуализировать и технически сложно пунктировать, возможность успешного нацеливания на фокус диаметром 2 мм с использованием таргетной биопсии составляет менее 26 % [30,31]. Кроме этого, в исследовании показано, что при оценке поражений для биопсии или хирургического планирования мпМРТ часто недооценивает размер поражения в среднем на 11 мм в диаметре и общий объем в 3 раза [32].…”
Section: клиническое применение таргетной биопсииunclassified
“…Additional factors important to confluent ablation zone include imaging co-registration error intrinsic in translation of MRI to TRUS (the imaging modality utilized for the majority of focal ablation technologies). Several studies have demonstrated that registration error between MRI and TRUS vary by size of the region of interest as well as registration technique, with elastic registration commonly improving this error ( 33 , 34 ). Treatment planning must also account for alterations in treatment anatomy secondary to treatment such as gland distortion from needle placement or energy absorption and patient movement during treatment ( 35 ).…”
Section: Ensuring Accurate Ablation—defining and Destroying The Indexmentioning
confidence: 99%